Implementation of Numbered Head Together Assisted by Number Card Media to Improve the Ability to Recognize Number Symbols at Al-Barokah Kindergarten Jambi City - Shalsha Widianti; Dian Syafitrah; Mukhlas Nugraha; Mardiana Mardiana; Mastikawati Mastikawati; Munawaroh Munawaroh (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to improve the ability of early childhood students to recognize number symbols through the implementation of the numbered head together method assisted by number card media at Al-Barokah Kindergarten, Jambi City. The background of this study is the low ability of children to recognize number symbols, including counting concrete objects, identifying numbers according to their symbols, and calculating quantities. Based on initial observations, the majority of children were at the "Not Yet Developing" (BB) and "Starting to Develop" (MB) stages, indicating a lack of mastery in basic numerical concepts. This research used the Classroom Action Research (CAR) method conducted in two cycles. During the pre-action phase, all children were categorized as BB (50%) and MB (50%), with none achieving the "Developing as Expected" (BSH) or "Very Well Developed" (BSB) stages. After interventions using the numbered head together method and number card media, the results showed significant improvements. At the end of Cycle I, 44% of the children reached the BSH stage, and 6% reached the BSB stage. A more significant improvement occurred in Cycle II, where 87% of the children were categorized as BSB, and 17% as BSH. By the end of Cycle III, no children remained in the BB or MB categories. The conclusion of this study indicates that the implementation of the numbered head together method assisted by number card media is effective in enhancing the ability of 5-6-year-old children to recognize number symbols at Al-Barokah Kindergarten. This method successfully helped children grasp numerical concepts in an interactive and enjoyable manner, improving their cognitive ability to recognize number symbols and their counting skills.